(untitled) (Contemporary Journal of Social Science Review, 2025)
Present research study appraises Garcia’s ‘We Are Not Born Submissive’, in the light of the feminist text and the criticism it attracts. This study examines how radical feminism theories have been able to shape the feminist ideologies and their relevance in the context of knowledge within feminism. The research is based on radical feminist theory and the use of textual analysis approach in the research process. The scholars utilize textual evidence in the book written by Garcia, and makes an analysis of the discourse regarding radical feminism thought. Two general objectives guided the research; all centered at the grounds where radical feminism and feminist discourse meet. The text-based sampling approach was deployed, and only primary data was used, with no other tools or secondary sources being part of study. The main purpose of the study was to answer the research question of how Garcia relates radical feminist theory to be able to examine feminist subject. By reading critically, it was clear that Garcia extensively incorporates the radical feminist theory in her discussion of subjectivity in women in the global context. This research is explicit about Garcia’s presentation of radical feminist theory in the novel, and this helps to shine on the abundance of implications that the predominance of males carries with it, the objection to submission, and the ferocity of women in different societal settings. The major findings of the study reveal that Garcia employs radical feminist views in order to denounce the triteness and social demands that women are subjected to, going against the conventional tales of female docility. This research study examines the selected text of Garcia with the correlate of radical feminism, therefore filling in the gap of knowledge concerning the work that Garcia does in relation to the subject of feminism, as well as the discourse of the feminist aspect of literary criticism. The selected works shows how Garcia is open to her application of radical feministic mindset and this allows in bringing into light the bulk of contexts the inferiority of men has with it, the protest against subjugation and the tenacity of women in other social entities. Such findings indicate that Garcia uses radical feminist ideas to criticize the stereotypes and social expectations women have to face going against the traditional storyline of the women as submissive. The researchers deeply study the selected work of Garcia at the interchange of radical feminism hence bridging the gap in information in relation to radical feminism aspect as an aspect of literary criticism.